1975
DOI: 10.1007/bf00039062
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical conditions in temporary ponds in the New Forest

Abstract: Seasonal fluctuations of the physicochemical conditions were recorded from five temporary ponds in the New Forest, over a period of two years . Diurnal fluctuations were also recorded . Physicochemical factors studied were pond volume ; air, water and substratum temperature ; water PH ; water conductivity ; and water dissolved oxygen level . The observed patterns of fluctuation are discussed and a concept of pond stability, to which the fluctuations may be related, is advanced .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The lowest pH values in March in pond 1 and in October in pond 2 might be associated with rainfall, high temperature and presence of high amount of free carbon dioxide. Khalaf and MacDonald (1975), Lakshminarayana (1965), Vyas and Kumar (1968) observed lower values of pH during monsoon. Banerjea (1967) reported that water with an almost neutral pH 6.5 to 7.5 is best suited for fish culture and average production is expected in the range of pH 6.5 to 8.5.…”
Section: Hydrogen Ion Concentration (Ph)mentioning
confidence: 92%
“…The lowest pH values in March in pond 1 and in October in pond 2 might be associated with rainfall, high temperature and presence of high amount of free carbon dioxide. Khalaf and MacDonald (1975), Lakshminarayana (1965), Vyas and Kumar (1968) observed lower values of pH during monsoon. Banerjea (1967) reported that water with an almost neutral pH 6.5 to 7.5 is best suited for fish culture and average production is expected in the range of pH 6.5 to 8.5.…”
Section: Hydrogen Ion Concentration (Ph)mentioning
confidence: 92%
“…Adaptation to the demanding conditions within ephemeral ponds has enabled a relatively diverse and unique ecology to inhabit them (Williams, 2006). Macroinvertebrates are the largest group recorded in ephemeral ponds (Zacharias et al, 2007), although microcrustacea are also very well represented (Khalaf and MacDonald, 1975). Williams (1997) has suggested there are two principle components to macroinvertebrate communities within ephemeral ponds.…”
Section: Ephemeral Pondsmentioning
confidence: 99%
“…Although the drying of ponds may be a routine hazard that many species have adapted to, the persistence and composition of macroinvertebrate communities may be influenced by other processes such as predation, locating a mate and other physicochemical and spatial parameters as well as hydroperiodicity (Jeffries, 1994;Spencer et al, 1999 Williams, 1996) which occur as water volume declines (in the summer months) and when the basin is initially inundated after the dry phase (Khalaf and MacDonald, 1975). Ephemeral ponds near…”
Section: Local (Physicochemical/biological) and Spatial (Connectivitymentioning
confidence: 99%
“…Low DO in summers may be attributed to low solubility of DO at high temperature in summers (Dutta and Patra, 2013; Gupta et al,, 2015) and increased load of organic matter and more consumption of DO for decomposition (Butcher et al, 1937;Thirupathaiah et al, 2012) while increased level of DO in winters may be due to inverse relation of DO solubility and temperature (Jhingaran, 1975;Khalaf and MacDonald, 1975).…”
Section: Dissolved Oxygen (Do)mentioning
confidence: 99%